Analysis of the Influence of Digital Banking, CAR, and BOPO on Bank Financial Performance for the 2014-2023 Period - Fauzul Azim Muhajir; Farah Wulandari Pangestuty (Contemporary Studies in Economic, Finance and Banking, 2025)
Digital transformation has become inevitable in the banking industry, with banks striving to adopt new technologies and enhance digital services to remain competitive and meet customer demands. Financial performance serves as a key indicator of a company’s stability and profitability. This study investigates the effect of digital banking, Capital Adequacy Ratio (CAR), and Operating Expenses to Operating Income (BOPO) on Return on Assets (ROA) in commercial banks during the period 2014–2023. Bank financial performance is measured through profitability (ROA). The study applies a quantitative research approach using secondary data obtained from six commercial banks. Multiple regression analysis with panel data is employed as the analytical method. The findings reveal that the independent variables collectively influence ROA. Partially, digital banking and BOPO exert a significant negative effect on ROA, whereas CAR shows no significant effect on profitability. Overall, digital banking, CAR, and BOPO jointly affect the ROA of commercial banks within the observed period.